Non-Pharmacological Interventions for Chronic Pain Management: A Narrative Review - Albesher, Mohammed; AlKhalifah, Mohammed; Hazazi , Abdulaziz; Hakeem , Ghassan; Almogbel, Bader (The Journal of Medicine, Law & Public Health, 2025)
Background: Chronic pain is a pervasive and debilitating condition affecting millions globally, leading to significant distress, disability, and economic burden. Characterized by persistent or recurring pain lasting beyond three months, it profoundly impacts quality of life, mental health, and socioeconomic well-being. Objectives: This comprehensive review critically evaluates the efficacy and safety of various non-pharmacological interventions for chronic pain management. Methods: A systematic search was conducted across PubMed, Scopus, CINAHL, and Web of Science databases for studies published in English between 2000 and 2024. Keywords related to chronic pain and non-pharmacological interventions were identified, including physical therapies, psychological therapies, and complementary and integrative medicine (CIM) modalities. Study selection focused on randomized controlled trials, controlled clinical trials, systematic reviews, cohort studies, and case-control studies involving adults with chronic pain. Results: Physical therapies, such as manual therapy, exercise therapy, and therapeutic modalities, demonstrate benefits in improving physical function and reducing chronic pain. Psychological therapies, including cognitive behavioural therapy (CBT), mindfulness-based stress reduction (MBSR), and acceptance and commitment therapy (ACT), are crucial for addressing the psychological and emotional dimensions of chronic pain. CIM modalities such as yoga, Tai Chi, acupuncture, and massage therapy offer complementary approaches. The strength of evidence varies across interventions, with CBT and exercise therapy supported by robust evidence, while other modalities require further investigation. Conclusions: This review underscores the importance of a multimodal approach to chronic pain management, integrating physical, psychological, and CIM therapies.